Students' Perceptions toward the Utilization of Web-Based AI Technology for English Language Learning in Higher Education: A Case Study at Institut Elkatarie: Students' Perceptions toward the Utilization of Web-Based AI Technology for English Language Learning in Higher Education: A Case Study at Institut Elkatarie - Kusuma Hadi; Rosliana Rosliana; Rekna Eka Purnamasari (Innovative Pedagogy and Education Studies, 2025)
This study aims to investigate students' perceptions toward the utilization of web-based Artificial Intelligence (AI) technology in English language learning in higher education, with a case study conducted at Institut Elkatarie. The research employed a descriptive qualitative approach supported by quantitative data. Data were collected through questionnaires and interviews involving undergraduate students who actively used web-based AI tools in their English learning activities. The findings reveal that most students have positive perceptions of web-based AI technology, particularly in enhancing learning flexibility, improving language skills (such as vocabulary, grammar, and writing), and providing immediate feedback. Students also perceive AI-based platforms as motivating, interactive, and helpful for independent learning. However, several challenges were identified, including limited digital literacy, overreliance on AI tools, and concerns about academic integrity. Despite these challenges, the study concludes that web-based AI technology has significant potential to support English language learning in higher education when integrated appropriately and accompanied by proper guidance from lecturers. The results of this study are expected to provide insights for educators and institutions in optimizing the use of AI technology to improve the quality of English language instruction.